Genetic structure and resistance to pyrethroids in Aedes aegypti populations in French Guiana: Preliminary results and perspectives - salgueiro, P. (Abstract Book of Amazonian Conference on Emerging and Infectious Diseases (ACEID), p. 42. STRONGER Project, Cayenne, French Guiana, 2014)
ackground: Aedes aegypti is vector of dengue and chikungunya viruses in French Guiana. A strong pyrethroid resistance has posed questions on the impact of vector control and resistance management. A prerequisite to improve those strategies is the investigation on population dynamics and factors which influence it. Therefore, we have implemented a population genetic study associated with deltamethrin resistance monitoring to provide further knowledge on these questions. Material and Methods: Two sites of 1 km² in Saint-Georges de l’Oyapock (SGO) and Cayenne (CAY) were prospected for mosquito immature stages in December 2013. F0 females were genotyped for 13 microsatellites and for the knockdown resistance associated mutation V1016I. Genetic diversity and differentiation indices were obtained in Arlequin software. Genetic structure among samples was tested in the program STRUCTURE. Evolutionary scenario probabilities and estimates were computed in DIY-ABC. Results: We detected the presence of two populations (k=2) congruent with each locality, with low but significant differentiation levels. Both populations exhibited similar effective population sizes and overall diversity. However, different evolutionary scenarios were obtained for each population. The V1016I kdr mutation is almost fixed in CAY population while SGO exhibited a larger proportion of heterozygotes. Conclusion: Genetic differentiation between the two populations suggests barriers to gene flow that may limit the exchange of resistance alleles. Therefore, the expansion of insecticide resistance in each population may also be due to local selective pressure. Additional spatial and temporal investigations are being conducted to confirm this hypothesis.